Answer:
We can conclude that only option B is correct.
Step-by-step explanation:
A. The equation 3(3x - 2) - 4 = 5x has a solution.
Solving it we get,
3(3x - 2) - 4 = 5x
⇒ 9x - 6 - 4 = 5x
⇒ 4x = 10
⇒ x = 2.5
B. The equation 4(2x - 3) - 5 = 4x has exactly one solution.
Solving it we get,
4(2x - 3) - 5 = 4x
⇒ 8x - 12 - 5 = 4x
⇒ 4x = 17
⇒ x = 4.25
C. The equation 5(3x - 2) - 2 = 3x also has exactly one solution.
Solving it we get,
5(3x - 2) - 2 = 3x
⇒ 15x - 10 - 2 = 3x
⇒ 12x = 12
⇒ x = 1
D. The equation 6(2x - 3) - 3 = 2x also has exactly one solution.
Solving it we get,
6(2x - 3) - 3 = 2x
⇒ 12x - 18 - 3 = 2x
⇒ 10x = 21
⇒ x = 2.1
Therefore, we can conclude that only option B is correct. (Answer)
Answer:
4
Step-by-step explanation:
you'd do 26-18 which will give the leftover money after paying for the two pizzas which equal 8
each soda costs 2 dollars so you would do 8 divided by 2 which is 4
The answer is: 83 + 12√35
(a + b)² = a² + 2ab + b²
In (2√5 + 3√7)², a = 2√5, b = 3√7
Just substitute a and b:
(a + b)² = a² + 2ab + b² = (2√5)² + 2 * 2√5 * 3√7 + (3√7)² =
= 2²√5² + 2 * 2 * 3 * √5 * √7 + 3²√7² =
= 4 * 5 + 12 * √(5*7) + 9 * 7 =
= 20 + 12 *√35 + 63 =
= 83 + 12√35
To answer your question: Rewrite <span>81<span>x2</span></span> as <span><span>(<span>9x</span>)</span>2</span>.<span><span><span>(<span>9x</span>)</span>2</span><span>−49</span></span>Rewrite 49 as <span>72</span>.<span><span><span>(<span>9x</span>)</span>2</span><span>−<span>72</span></span></span> Both terms are perfect squares, factor using the difference of squares formula, <span><span><span>a2</span><span>−<span>b2</span></span></span>=<span><span>(<span>a+b</span>)</span><span>(<span>a<span>−b</span></span>)</span></span></span> where <span>a=<span>9x</span></span> and <span>b=7</span>.<span><span>(<span><span>9x</span>+7</span>)</span><span>(<span><span>9x</span><span>−7</span></span><span>)</span></span></span>
Answer:
-3
Step-by-step explanation:
3+x=0
subtract 3 from 3, 0
subtract 3 from 0, -3